If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 10 + 3x Solving 1 = 10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + -3x = 10 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + -3x = 10 + 0 1 + -3x = 10 Add '-1' to each side of the equation. 1 + -1 + -3x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 10 + -1 -3x = 10 + -1 Combine like terms: 10 + -1 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 8(3x-5)-4(2x+3)=12 | | 25=4x-3 | | X+x/4=15 | | 5=15+2x | | 8=4x-2 | | 6xy-9yx+4xy= | | 5x*5y=32 | | a+5+2a-2= | | 5p-8=3(4-p) | | 17x^3-2x^2-20x+8=0 | | 4x-5x+y+6y= | | 5(x+2)=7 | | 10x+6=7x | | 8mn+2mn-6mn= | | pq-8pq+9pq= | | 92748727x=835295 | | 6ab-5ab= | | 3x^2+10=P | | 2x+2y=88 | | x2-5x=-9/4 | | 88-7x=29x+20 | | 3x+7=173-7x | | X=20-4y | | 109-3x=6-7x | | x=3.887482194 | | Y=2(6)-3 | | Y=2(4)-3 | | Y=2x(-2)-3 | | 2x^3+x+8=0 | | 15b+20b^3=0 | | 7n^2-8n=0 | | x2+x=19/4 |